PERASAAN KEPUASAN MUALAF DALAM KEHIDUPAN ISLAM: KEPENTINGAN DAN IMPLIKASINYA DARI ASPEK DAKWAH - Mariam Abd Majid (IAIN Padangsidimpuan, 2018)
This article is intended to introduce the concept of satisfaction associated with the lives of the converts in life after Islam. Writing focuses on the elements of satisfaction in the aspect of faith, practice of worship (syariat) and aspects of morality. This data is obtained through content analysis of the Qur'anic verses and Hadiths and documentation sources. It is found that the satisfaction of the mualaf is manifested when the situation has come to something that is desired or gets what is expected in accordance with the goals set out to achieve. The sense of satisfaction of mualaf can be felt when it comes to the sweetness of the result of a steadfast faith in Allah SWT, to gain the result of the charitable acts performed in accordance with the hadeeth of the Shari'a and to receive the noble moral service. This effort requires the support and assistance that is the responsibility of all Muslims. Keywords: Feeling Satisfaction, Mualaf, Islamic Life, Da'wah